Water Sensitivity and Structural Properties of Loess - Longfei Zhang; Zaiqiang Hu; Hongru Li; Haicheng She; Xiaoliang Wang; Xi Yang; Xiaoning Han (Advances in Civil Engineering)
Loess has unique water sensitivity due to its distinct formation environment. The structure of loess is undercompactness, weak cementation, and porousness. The water sensitivity of loess directly leads to many environmental problems and geological hazards, including subgrade subsidences, slope collapse or failures, and building cracking. To reveal the relationship between water sensitivity and loess structure, confined-compression collapsibility tests and triaxial-collapsibility tests were performed on loess in different areas. The collapsibility coefficient, porosity ratio, and collapsibility rate were analyzed. Results show that the collapsibility process of loess can be divided into three stages: wetting, softening, and settling. The collapsibility sensitivity of loess is determined primarily by its structural and hydraulic state.